Strategi Pembelajaran Akidah Akhlak dalam Membentuk Karakter Siswa di SMP Qur’ani Asyarichin - Salim, Salim; Azis, Sumarno; Nur Amanah, Lisa (Diksi: Jurnal Pendidikan dan Literasi, 2023)
Formal educational institutions with the concept of pesantren (Islamic boarding schools) certainly have specificity in the curriculum used. One such institution is Qur'ani Asyarichin Junior High School located in Tajinan village, Malang district. The problem to be explored is related to the character of students. The purpose of this research is to analyze the learning of akidah akhlak to improve the personality of students. This research model is based on a qualitative model with a case-study approach. Then the data analysis starts with summarizing, examining, and presenting the data. The results showed that Qur'ani Asyarichin Junior High School still uses the 2013 curriculum combined with the pesantren curriculum. The learning methods applied are uswatun hasanah, halaqah and mauidhoh methods. The characters that emerge from students during the learning process of akidah akhlak are very diverse, ranging from disciplined, responsible, creative, innovative, independent, and religious characters